2016
DOI: 10.1128/jvi.02793-15
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Array of New Viral Sequences Identified in Worldwide Populations of the Asian Citrus Psyllid (Diaphorina citri) Using Viral Metagenomics

Abstract: The Asian citrus psyllid, Diaphorina citri, is the natural vector of the causal agent of Huanglongbing (HLB), or citrus greening disease. Together; HLB and D. citri represent a major threat to world citrus production. As there is no cure for HLB, insect vector management is considered one strategy to help control the disease, and D. citri viruses might be useful. In this study, we used a metagenomic approach to analyze viral sequences associated with the global population of D. citri. By sequencing small RNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 99 publications
3
68
2
Order By: Relevance
“…This adds to the findings of Singh and co-authors who demonstrated the circulation of RNA viruses among bees through pollen-vectoring [22]. Another viral match included the RdRp of a tombusnodavirus related to the psyllid virus DcACV [56] and the honey bee CBPV. This was an unusual finding because these viruses lack a 3’ end polyA-tail [57] and are theoretically not retained by polyA+ mRNA enrichment.…”
Section: Discussionsupporting
confidence: 55%
“…This adds to the findings of Singh and co-authors who demonstrated the circulation of RNA viruses among bees through pollen-vectoring [22]. Another viral match included the RdRp of a tombusnodavirus related to the psyllid virus DcACV [56] and the honey bee CBPV. This was an unusual finding because these viruses lack a 3’ end polyA-tail [57] and are theoretically not retained by polyA+ mRNA enrichment.…”
Section: Discussionsupporting
confidence: 55%
“…Kinkell virus, along with transcriptome sequences from the fly genera Bactrocera 62,66 and Ceratitis 63 , the beetle Colaphellus 67 , the thrip Frankliniella 68 , and the spider Latrodectus 69 , appears to define a major new clade that falls within or close to the Iflaviruses (Fig 2 D). Similarly, Corseley virus, which is almost identical to transcriptome sequences from D. pseudoananassae 70 and is related to transcriptome sequences from the bug genus Lygus 71 and the beetle genus Anoplophora 72 , appears to define an entirely new group of viruses distantly related to Tombusviridae and the recently-described Diaphorina citri associated C virus 73 (which is itself closely related to the newly identified Tartou virus of S. deflexa; Fig 2 E).…”
Section: New Viruses Without Close Relativesmentioning
confidence: 73%
“…Fifteen of remaining 23 putative viruses in the present study are extremely closely related to known insect viruses or virus-like sequences from insect transcriptomes (Fig 1, Fig 2), and/or are present at such high levels (greater than 10% of host COI in the cases of Muthill virus and Eridge virus), that is seems likely that the associated drosophilid is indeed the host. 73 , Tartou virus and Corseley virus from the Drosophilidae, and transcripts from various invertebrates. All three groups appear to represent common and widespread infections of invertebrates that warrant taxonomic recognition.…”
Section: New Viruses Of Drosophilamentioning
confidence: 99%
“… Culture‐independent techniques have captured how microbial community composition in insects varies largely in time and space‐in response to diet, geography, season, and developmental stage (Hu et al., ; Wilhelm et al., ; Chaplinska et al., ; Lv et al., ; Vacchini et al, ; Bascuñán et al., ). The relevance of these parameters might vary according to the microbial groups, with environmental factors being more important for bacteria and fungi than in shaping the viral communities (Nouri et al., ). How do these variations in microbiome composition affect the interplay among these members of the microbiome, and how does that affect pest insects?…”
Section: Discussionmentioning
confidence: 99%